LEGAL ASPECTS OF THE RESOLUTION OF CONTRACTUAL DISPUTES ARISING FROM THE CROSS-BORDER USE OF ARTIFICIAL INTELLIGENCE, AUTOMATED DECISION MAKING AND SMART CONTRACTS (Journal of Science-Innovative Research in Uzbekistan, 2024)
This article analyzes the role of artificial intelligence technologies and smart contracts in legal relations, and the legal mechanisms for resolving disputes that arise during their use. Proposals for improving national legislation in this area have also been developed.